HLA class I molecules are not transported to the cell surface in cells infected with herpes simplex virus types 1 and 2. - Hill, AB; Barnett, B; McMichael, A; McGeoch, D (1994)
To assess the effect of herpes simplex virus (HSV) on assembly and transport of class I MHC molecules, we compared class I MHC immunoprecipitated from metabolically labeled infected and uninfected human dermal fibroblasts. The immunoprecipitates were analyzed by isoelectric focusing, allowing identification of individual class I alleles and assessment of transport through the Golgi apparatus by the sialation of carbohydrate residues. In cells infected with wild-type HSV, class I synthesis was reduced or abolished because of the host protein synthesis shutoff function of the UL41 gene product. In cells infected with mutant viruses of both HSV-2 strain G and HSV-1 strain 17 that lack the UL41 gene, class I HLA molecules failed to become sialated, suggesting that they were not transported to the Golgi apparatus. In contrast, transferrin receptor was normally sialated in both infected and uninfected cells. Drug treatments of cells to restrict viral gene expression suggested that an early gene or genes were responsible for the effect. A pulse chase showed that class I molecules were synthesized in normal amounts in infected cells, but that heavy chains were retained in a sialyl transferase negative compartment either stably associated with beta 2m or as free heavy chain in a pattern that is characteristic for each class I allele. HSV is thus the fourth example of a DNA virus that interferes with class I assembly or transport.